Development of a solid-phase microextraction method for fast analysis of cyclic volatile methylsiloxanes in water. (July 2020) - Zhang, Lifang; Jiang, Ruifen; Li, Wanbin; Muir, Derek C.G.; Zeng, Eddy Y.
Abstract: Cyclic volatile methylsiloxanes (cVMS) are widely used in consumer products and commonly detected in the environment. There are challenges in the analysis of cVMS because of their ubiquitous use which can introduce high background contamination. The current study introduces a sample preparation method based on headspace of solid-phase microextraction (SPME) for monitoring the cVMS in waters. Efforts were made to reduce the background contamination during sample preparation and instrument analysis. A laboratory prepared MIL-101 coating was prepared using polysulfone instead of polydimethylsiloxane as adhesive to avoid the contamination. The extraction performance of the MIL-101 fiber was optimized and evaluated. The optimized extraction time and temperature were 60 min and 40 °C, respectively. The method quantification limits of the MIL-101 fiber for octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5) and dodecylcyclohexasiloxane (D6) in water were 0.15 ng mL −1, 0.14 ng mL −1, and 0.27 ng mL −1, respectively. The extraction efficiency of the proposed MIL-101 fiber was comparable to the commercial polydimethylsiloxane/divinylbenzene fiber. The developed method was applied to analyze the cVMS in wastewater treatment plant and the concentrations in the barscreen and in the aeration tank ranged from 0.73 to 3.3 ng mL −1 and 7.74–85.1 ng mL −1, respectively. The MIL-101 fiber was also applied to study the photodegradation of the cVMS in water under simulated sunlight. Approximately 25%, 20%, and 45% of D4, D5, and D6, respectively, were degraded after 10 h exposure. Graphical abstract: Image 1 Highlights: MIL-101 was used as the SPME fiber coating to extract the cVMS from water. Background contamination during sample preparation were reduced to the maximum extent. SPME method was applied to study the distribution of cVMS in WWTP and the photodegradation in water.